Penyuluhan terhadap orang tua dalam mendidik perilaku beribadah anak - Rosmerry, Rifa Fauzi (Jurnal Abmas, 2024)
This service is carried out by conducting counseling, which aims to strengthen the role of parental Islamic education to be more intensive and children’s worship behavior. This service aims to enhance the role of parental Islamic education to be more intensive, improve children’s worship behavior, and bring their relationship with God closer. The service method includes planning, implementation, and evaluation with the participants of this service and research activity, as well as parents of students and children who attend elementary school through junior high school. Community service activities are counseling parents about the importance of Islamic education in children’s worship behavior and coaching children to be more active in worshiping God. Based on the results of community service activities and the discussion previously described, the results show that parents’ role is significant in children’s worship behavior. Parents who order their children to worship so that they become more diligent in worshiping at the mosque. Meanwhile, parents’ indifference to their children’s worship behavior causes them to rarely perform routine worship such as prayer, recitation, and reading the Qur’an. Abstrak Pengabdian ini dilakukan dengan mengadakan penyuluhan yang bertujuan menguatkan peran pendidikan Islam orang tua supaya lebih intensif lagi serta perilaku beribadah anak. Tujuan pengabdian ini untuk menguatkan peran pendidikan Islam orang tua supaya lebih intensif lagi serta perilaku beribadah anak supaya lebih baik dan hubungannya dengan Sang Pencipta dapat lebih dekat. Metode pengabdian meliputi perencanaan, pelaksanaan, dan evaluasi dengan peserta kegiatan pengabdian dan penelitian ini merupakan orang tua siswa serta anak yang bersekolah di jenjang SD sampai SMP. Bentuk kegiatan pengabdian adalah penyuluhan kepada orang tua tentang pentingnya peran pendidikan Islam orang tua terhadap perilaku beribadah pada anak dan pembinaan terhadap anak supaya lebih giat dalam beribadah kepada Tuhannya. Berdasarkan hasil kegiatan pengabdian kepada masyarakat dan pembahasan yang telah dipaparkan sebelumnya, hasilnya dapat dilihat bahwa peran orang tua sangat penting dalam perilaku beribadah pada anak. Orang tua yang memerintahkan anak untuk beribadah sehingga anak menjadi lebih rajin beribadah di masjid. Sedangkan, orang tua yang acuh terhadap perilaku beribadah anaknya menyebabkan mereka jarang melakukan ibadah rutin seperti salat, mengaji, dan membaca Al-Quran. Kata Kunci: orang tua; penyuluhan; perilaku beribadah.